2005
DOI: 10.1155/bca.2005.299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization And Antitumor Activity OfCopper(II) Complexes, [CuL2] [HL1-3=N,N‐Diethyl‐N′‐(R‐Benzoyl)Thiourea (R=H, o‐Cl and p‐NO2)]

Abstract: The copper (II) complexes (CuL2) were prepared by reaction of Cu(CH3COO)2 with the corresponding derivatives of acylthioureas in a Cu:HL molar ratio of 1:2. Acylthiourea ligands, N,N-diethyl-N'-(R-benzoyl) thiourea (HL1-3) [R=H, o-Cl and p-NO2] were synthesized in high yield (78-83%) and characterized by elemental analysis, infrared spectroscopy, 1H and 13C NMR spectroscopy. The complexes CuL2 were characterized by elemental analysis, IR, FAB(+)-MS, magnetic susceptibility measurements, EPR and cyclic voltamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 1 publication
2
23
0
1
Order By: Relevance
“…The free ligands present an intense band in the region between 1800 and 1610 cm -1 , which is assigned to vC=O stretching vibrations [28,29,55] and is absent in the spectra of the complexes, evidencing …”
Section: Infrared and Ultraviolet-visible Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The free ligands present an intense band in the region between 1800 and 1610 cm -1 , which is assigned to vC=O stretching vibrations [28,29,55] and is absent in the spectra of the complexes, evidencing …”
Section: Infrared and Ultraviolet-visible Spectroscopymentioning
confidence: 99%
“…The complexes exhibit νRu-P stretching in the range 521-511 cm -1 . Also, the νRu-S, νRu-N and νRu-O stretching vibrations occur as weak bands in a region of low intensity at about 500-350 cm -1 [55].3.4 Multinuclear 31 P{ 1 H}, 1 H and 13 C NMR experimentsIn the 1 H NMR spectra of the free ligands, a shoulder band corresponding to a singlet of the N-H group proton is observed in the region of 8.10-8.70 ppm[28,29,50]. This kind of signal is absent in the spectra of the complexes, indicating the deprotonation of the acylthioureide group by the coordination of the ligand, which acts as a monoanionic species, to the metal.…”
mentioning
confidence: 99%
“…It has been reported that substituted acylthiourea ligands might act as monodentate sulfur donors, bidentate oxygen and nitrogen donors. They could also coordinate through the keto-or enolthione form, depending of the ligands themselves, and the metal ions and counter-anions used [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Polysubstituted acylthiourea and its fused heterocycle derivatives were utilized as inhibitors of influenza virus [18]. In addition, acylthiourea derivatives and their coordination compounds exhibit strong antitumor and anticancer activity [19]. Benzoylphenylthiourea derivatives possess potent antitumor activity against both pancreatic and prostate cancer cell lines [20].…”
Section: Introductionmentioning
confidence: 99%